भारतीय जल विज्ञान : पुरातन जल विज्ञान पर भारतीय लोक चिन्तकों के विचार - Mishra 'Madhukar', Mahesh Kumar (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2010)
The book describes the various thoughts and analytical approaches of Hydrology in ancient India.
Bharatiya Jal Vigyaan : Puratan Jal Vigyan par Bharatiya Lok Chintakon ke Vichaar
Keywords: Hydology; Hindi